FARMAKOGENETIC ASPECTS OF TREATMENT OF AN ARTERIAL HYPERTENSIA AT PATIETNS OF A CHRONIC PYELONEPHRITIS - Mormol, I.A. (World of Medicine and Biology, 2014)
Now necessity of the strict control arterial pressure (AP) is conventional at chronic diseases of kidneys. Inhibitors of receptors AT1R (BAR) are recognized all over the world as preparations of the first of some for treatment of renoparenchimal hypertensia . The purpose research – to study of clinical effect of Candesartan at patients with renoparenchimal hypertensia depending on a genotype. Survey 50 patients with inspected patients with renoparenchimal hypertensia on a background of chronic pyelonephritis, polymorphism of gene of angiotensin ll of the first type is certain. Patients appointed Kandesartan in doses of 8-32 мг, observed in current of 12 months. By results of research the genotype AA is revealed at 46%, AC at 48%, CC at 6% of patients. Allel A it is revealed in a genotype of 94%, allel C - 54% of patients of renoparenchimal hypertensia. A target level the AP will reach at 94,3% patients. Kandesartan has shown high clinical effect at all variants of polymorphism of gene AT1R.
Keywords: renoparenchimal hypertensia; gene of receptor of angiotensin ll of the first type; candesartan